In vitro chondroprotective potential of Senna alata and Senna tora in porcine cartilage explants and their species differentiation by DNA barcoding-high resolution melting (Bar-HRM) analysis - Siriwan Ongchai (2019)
© 2019 Ongchai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Senna species and anthraquinone derivatives generated by these organisms, rhein and aloe-emodin, exert anti-inflammatory effects. These species present a similar morphology but produce different ingredients when they are used as medicinal products. In this study, a DNA barcoding- (Bar-) high-resolution melting (HRM) technique was developed using internal transcribed sequence 2 (ITS2) to differentiate between Senna alata and Senna tora as a result of significant differences in their melting profiles. We used this approach for confirmation of S. alata and S. tora raw materials, and we examined the chondroprotective properties of the ethanolic extracts of S. alata and S. tora using a porcine model of cartilage degradation induced by a combination of interleukin-17A (IL-17A) and IL-1β. We found that both Senna ethanolic extracts, at a concentration of 25 μg/mL, effectively prevented cartilage degradation. Rhein and aloe-emodin were present in the extract of S. alata but not in that of S. tora. We observed a reduction in the release of sulfated glycosaminoglycans (S-GAGs) and hyaluronic acid (HA) into media in both treatments of Senna extracts, which indicated proteoglycan preservation in explant tissues. These results suggest that neither rhein nor aloe-emodin are the main factors responsible for cartilage-protecting properties. Taken together, results show that both S. alata and S. tora are promising for further development as anti-osteoarthritic agents and that Bar-HRM using ITS2 could be applied for species confirmation with Senna products.